2015
DOI: 10.1371/journal.ppat.1004785
|View full text |Cite
|
Sign up to set email alerts
|

Positive Role of Promyelocytic Leukemia Protein in Type I Interferon Response and Its Regulation by Human Cytomegalovirus

Abstract: Promyelocytic leukemia protein (PML), a major component of PML nuclear bodies (also known as nuclear domain 10), is involved in diverse cellular processes such as cell proliferation, apoptosis, gene regulation, and DNA damage response. PML also acts as a restriction factor that suppresses incoming viral genomes, therefore playing an important role in intrinsic defense. Here, we show that PML positively regulates type I interferon response by promoting transcription of interferon-stimulated genes (ISGs) and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 58 publications
(70 reference statements)
6
107
0
Order By: Relevance
“…7). This finding confirms and complements the results of a study by Kim and Ahn on the role of PML in type I interferon response, which was published while this paper was in preparation (59). By using PML knockdown cells, they demonstrated that PML is required for an efficient accumulation of STAT proteins and their phosphorylated forms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…7). This finding confirms and complements the results of a study by Kim and Ahn on the role of PML in type I interferon response, which was published while this paper was in preparation (59). By using PML knockdown cells, they demonstrated that PML is required for an efficient accumulation of STAT proteins and their phosphorylated forms.…”
Section: Discussionsupporting
confidence: 88%
“…6B and 8C). Thus, these results complement the experiments of Kim and Ahn (59), which analyzed the consequences of deletions within the PML-binding domain IE1 CORE or the STAT interaction region on the capacity of IE1 to inhibit type I IFN signaling. They suggested a requirement of both PML binding and STAT binding for an efficient inhibition of the interferon response by IE1 and proposed sequestration of PML/STAT complexes as a mechanistic basis.…”
Section: Discussionsupporting
confidence: 79%
“…It has been demonstrated that HDAC1 specifically coactivates the promyelocytic leukemia zinc finger and promyelocytic leukemia proteins that are involved in type I IFN-mediated innate immune response and subsequent expression of ISGs like viperin (32,37). The above data demonstrated that class I and class II HDAC activity is required for the IAV-induced host type I IFN-mediated antiviral response and the expression of ISGs, including viperin.…”
Section: Fig 3 the Overexpression Of Hdac1 Inhibits Iav Infection (Amentioning
confidence: 81%
“…Several previous reports have highlighted a complex role of the IFN pathway in response to HCMV. The activity of the promyeolcytic leukemia protein, a regulator of type I IFN response, is counteracted by HCMV-encoded immediate early 1 protein (IE1) (6). A cytoplasmic dsDNA sensor, ZBP1, activates IRF3 on infection, and its overexpression inhibits HCMV replication (7).…”
Section: Ripk2mentioning
confidence: 99%